Home-based shared book reading and developmental outcomes in young children: a systematic review with meta-analyses - Galea, Claire; Jones, Alana; Ko, Katherine; Salins, Andrea; Robidoux, Serje; Noble, Clayton; McArthur, Genevieve (Frontiers in Language Sciences, 2025)
The aim of this systematic review was to measure the strength of the relationship between home-based shared book reading and child development. We identified 46 studies (N = 56,576) that provided quantitative data on the home literacy environment and developmental outcomes for groups of 10 or more children (maximum N = 10,533) who had a mean age of <4 years, and had not commenced compulsory, formal schooling. Most studies (n = 28/46; 61%, N = 24,859) reported correlation coefficients, which were used to calculate mean effect sizes in a series of meta-analyses. The results estimated large and statistically significant relationships between home-based shared book reading and developmental outcomes [r = 0.303, 95% CI = (0.258, 0.349)], language outcomes [r = 0.381, 95% CI = (0.289, 0.474)], and vocabulary outcomes [r = 0.314, 95% CI = (0.291, 0.336)]; as well as a moderate and significant relationship between frequency of home-based shared book reading and expressive vocabulary [r = 0.259, 95% CI = (0.099, 0.419)]. These findings indicate that home-based shared book reading is positively related to various developmental outcomes, particularly spoken language skills.